Pilot study of the effects of lisdexamfetamine on cocaine use: A randomized, double-blind, placebo-controlled trial. (1st August 2015) - Mooney, Marc E.; Herin, David V.; Specker, Sheila; Babb, David; Levin, Frances R.; Grabowski, John
Highlights: Lisdexamfetamine (LDX) 70 mg QD vs. placebo for 14 weeks in 43 cocaine-dependent treatment seekers. Twice weekly urine tests for benzoylecgonine analysis (BE; a cocaine metabolite). No significant differences between treatment groups in cocaine use rates. LDX-treated subjects reported significantly less craving for cocaine. Abstract: Background: Amphetamine analogs have been demonstrated to have some efficacy in reducing use in cocaine dependent individuals. However, these agents also have potential for abuse. Lisdexamfetamine (LDX), a lysine + dextroamphetamine formulation, has been approved for the treatment of Attention-Deficit/Hyperactivity Disorder (ADHD) and as a prodrug, has less abuse potential. Objective: This pilot study sought to evaluate the safety, tolerability, and efficacy of LDX as a candidate treatment for cocaine dependence. Methods: A randomized, double-blind, placebo-controlled parallel group study served to evaluate LDX in 43 cocaine-dependent individuals: (1) placebo (PBO; 0 mg, n = 21), (2) LDX (70 mg, n = 22). Participants received medication for 14 weeks. Cocaine use was determined based on urine analysis for benzoylecgonine (BE; a cocaine metabolite). Results: Retention rates were higher though not significantly different in the PBO (71.4%) than the LDX condition (57.1%). Compared to those in the PBO condition, those receiving LDX were more likely to report experiencing ( p s < 0.05) diarrhea (45.5% vs. 14.3%), headaches (45.5% vs. 9.5%), and anxiety (31.8% vs. 4.8%). No differences in medication conditions were observed for blood pressure, heart rate, or body weight. In the randomized sample, no differences in cocaine use were seen. Those receiving LDX reported significantly less craving for cocaine than participants receiving PBO. Conclusions: LDX did not significantly reduce cocaine use compared to PBO in the randomized sample.